TAS2R5 screening reveals biased agonism that fails to evoke internalization and downregulation resulting in attenuated desensitization - Donghwa Kim; Hannah R. Strzelinski; Stephen B. Liggett (PLoS ONE, 2025)
The bitter taste receptor type 5 (TAS2R5) is expressed on multiple cell types and appears to be a suitable target for novel agonist treatments across multiple therapeutic areas. Like most G protein coupled receptors (GPCRs), TAS2R5 undergoes functional desensitization with prolonged agonist exposure which could limit effectiveness. The net loss of cellular receptors (termed downregulation) is a prominent mechanism of long-term desensitization; we screened 13 agonists for downregulation of receptor protein in TAS2R5-transfected HEK-293T and airway smooth muscle cells in culture, searching for pathway selectivity favoring G protein coupling over downregulation. The benchmark agonist 1,10-phenanthroline (denoted T5-1) evoked as much as 75% downregulation of TAS2R5 protein expression with 18-24 hrs of agonist exposure, while an analogue of T5-1 (denoted T5-12) caused a 2-3 fold increase in expression. Functionally, T5-1 and T5-12 were found to be full agonists when measuring [Ca2+]i or ERK1/2 stimulation. The T5-12 phenotype was found to be due to agonist-induced stabilization of the receptor confining it to the cell membrane with subsequent failure to undergo internalization and receptor degradation. This occurred despite normal (referenced to T5-1) GRK-mediated receptor phosphorylation and β-arrestin recruitment by T5-12. Consistent with the lack of downregulation, T5-12 evoked much less functional desensitization of the [Ca2+]i (43% vs 78%) and ERK1/2 (64% vs > 95%) responses compared to T5-1, respectively. We conclude that TAS2R5 pathway signaling is malleable to a more favorable therapeutic profile by agonist-receptor interactions that preserve primary signaling and minimizes desensitization.